Pandemic and Education: notes from the Brazilian context - Brum, Lucas Pacheco; Magalhães, Marcus Vinícius Silva; Wolffenbüttel, Cristina Rolim; Souto, Carlos Augusto Pinheiro; Leite, Maria Cecilia Lorea (International Journal for Innovation Education and Research, 2021)
This is an essay that addresses issues related to learning and its possible enhancements through the use of technologies. In the year 2020, amid the moment when all of humanity was affected due to the advent of a pandemic, caused by COVID-19, abrupt changes occurred in all instances. Schools did not go unscathed by all the changes that millions of people were affected by. In the present essay, the authors discuss the problems of this pandemic moment, inviting readers to think about the current moment, having at sight the unequal possibilities that have risen by the educational process mediated by technologies and digital medias.